Selective prevention of cardiometabolic diseases: activities and attitudes of general practitioners across Europe - de Waard, Anne-Karien M; Hollander, Monika; Korevaar, Joke C; Nielen, Mark M J; Carlsson, Axel C; Lionis, Christos; Seifert, Bohumil; Thilsing, Trine; de Wit, Niek J; Schellevis, François G (European journal of public health, 2019)
Background: Cardiometabolic diseases (CMDs) are the number one cause of death. Selective prevention of CMDs by general practitioners (GPs) could help reduce the burden of CMDs. This measure would entail the identification of individuals at high risk of CMDs-but currently asymptomatic-followed by interventions to reduce their risk. No data were available on the attitude and the extent to which European GPs have incorporated selective CMD prevention into daily practice. Methods: A survey among 575 GPs from the Czech Republic, Denmark, Greece, the Netherlands and Sweden was conducted between September 2016 and January 2017, within the framework of the SPIMEU-project. Results: On average, 71% of GPs invited their patients to attend for CMD risk assessment. Some used an active approach (47%) while others used an opportunistic approach (53%), but these values differed between countries. Most GPs considered selective CMD prevention as useful (82%) and saw it as part of their normal duties (84%). GPs who did find selective prevention useful were more likely to actively invite individuals compared with their counterparts who did not find prevention useful. Most GPs had a disease management programme for individuals with risk factor(s) for cardiovascular disease (71%) or diabetes (86%). Conclusions: Although most GPs considered selective CMD prevention as useful, it was not universally implemented. The biggest challenge was the process of inviting individuals for risk assessment. It is important to tailor the implementation of selective CMD prevention in primary care to the national context, involving stakeholders at different levels.
Keywords: dospělí; lékařská praxe - způsoby provádění; Švédsko; průzkumy a dotazníky; Female; Netherlands; Dánsko; postoj zdravotnického personálu; Adult; ženské pohlaví; Greece; Surveys and Questionnaires; lidé; praktičtí lékaři; Denmark; Attitude of Health Personnel; Risk Factors; Nizozemsko; Male; Sweden; Cardiovascular Diseases; Czech Republic; primární zdravotní péče; rizikové faktory; kardiovaskulární nemoci; Primary Health Care; Česká republika; lidé středního věku; mužské pohlaví; General Practitioners; Middle Aged; Řecko; Practice Patterns, Physicians'; Humans